Conformity to the charter for visits from pharmaceutical representatives. Issue 2 (12th March 2012) - Leroy, B.; Lajoinie, A.; Ducher, M.; Maire, P.; Bourguignon, L.
Abstract : Background: Visits from pharmaceutical representatives (PRs) are controlled in France by regulations, but also by a Charter of good practice, drafted by an organisation which represents 270 drug companies (LEEM). The goal is to control promotional visits from pharmaceutical laboratories to healthcare professionals. Purpose: The goal of this study was to measure compliance with the conditions of this charter by participating pharmaceutical companies. Materials and methods: An assessment grid was drafted to determine compliance to prohibitions and obligations concerning the information provided during visits from PR. Thus after each visit by a PR, The authors collected information identifying the PR and his company, the method of comparing a competitor's specialty, any donations (gifts, invitations, samples), promotion of proper use and documents provided. Results: The authors studied 20 visits from PRs. The PR's obligation to identify himself and his company was respected in 75% of cases. All of the documents and obligatory information were only provided in 5% of cases (notification from the French National Authority for Health (HAS) was absent in 90% of cases). During 80% of these meetings the PR made a comparison with competitor's drugs, which was associated with negative remarks in 44% of cases. The PR promoted cases of use outside those that had received marketing approval in 35% of conversations. Invitations to scientific meetings, promotional events and/or training were not offered to any of the participants of these meetings. On the other hand gifts or samples were offered at the end of these meetings in 20% of cases. Prohibited practices were observed in a total of 85% of cases. Conclusions: Our results suggest that at present hospital visits by PRs do not respect the commitments made by the pharmaceutical industry, and do not make it possible to ensure that honest information is provided or information that favours the proper use.